If and how do 360° videos fit into education settings? Results from a scoping review of empirical research. (6th May 2022) - Ranieri, Maria; Luzzi, Damiana; Cuomo, Stefano; Bruni, Isabella
Abstract: Background: Over recent years, interest towards the use of immersive technologies has grown in parallel with the lowering of equipment costs: educators have started embedding them into their teaching practices at different levels of the educational system, from primary school to higher education. In general, immersive technologies are seen as suitable tools to live vicarious experiences, when the reality is hardly accessible, for instance due to safety issues. Objectives: In this paper, we focus on 360° videos with the aim of developing a more systematic and evidence informed approach to the understanding of the educational uses of 360° in different educational contexts. Methods: A scoping literature review approach has been adopted in order to obtain a comprehensive insight based on objective, replicable and transparent procedures. Results and conclusions: The review includes studies published from 2016 onwards. According to the findings, 360° videos are more suitable for disciplines requiring careful observation of how knowledge is transferred into practice and where practical scenarios are involved: 360° videos have positive effects on learning, especially referring to motivation, attentiveness, information retention and transfer of knowledge. However, as for learners' reactions, physical discomfort is reported, mainly associated with the use of HMD. In addition, challenges, and barriers to the educational use of 360° video should be further analysed, since up to now logistical constraints have limited the studies to a very small sample population, without the possibility of providing suggestions for a wider adoption at organisation and institution level. Implications: As 360° videos are reported to be promising in fostering learning processes, students' engagement, and information retention, further studies are recommend to cover the current gaps in the literature, particularly focusing on drawbacks and organizational challenges. Lay Description: What is currently known about the subject matter?: Immersive technologies are knowing increased use in recent years. Some evidence on their positive influence on learning emerged. Empirical research on the pedagogical affordances of 360° video is still limited. What the paper adds?: It identifies the most common teaching methods combined with 360° video. It provides a systematic understanding of 360° video learning gains. It helps catching possible drawbacks of 360° video. Implications of study findings for practitioners: It encourages an aware use of 360° video to increase students' engagement. It may inspire the design of effective learning experiences. It focuses on suitable solutions when physical experiences are not possible—as in a pandemic.